Comparison of Contrast-Enhanced Ultrasonography to Color Doppler Ultrasound in Evaluation of Carotid Body Tumors - Gu, Guangchao; Zhang, Xiaoyan; Shen, Junyue; Gulidanna, Shayan; Gao, Qiong; Shao, Jiang; Liu, Bao; Zhang, Bo; Zheng, Yuehong (Frontiers in Oncology, 2022)
Objective: The objectives of this study were to prospectively 1) explore the characteristics and enhanced patterns of carotid body tumors (CBTs) at color Doppler Ultrasound (CDU) and contrast-enhanced ultrasonography (CEUS) qualitatively and quantitatively, and 2) compare CDU and CEUS for their morphology and vascularity signature. Methods: CDU and CEUS with Sonovue® were used to evaluate 25 CBT lesions. The comparison between these ultrasonic modalities included size, Shamblin type, vascularity and feeding vessels of the lesion areas. The time-intensity curve (TIC) analysis was used to obtain the dynamics of the contrast-enhancement features of CBTs. Results: The TIC analysis presented a fast wash-in (wash in time (WIT): 3.00  1.11s, mean ± SD) and slow wash-out (wash out time (WOT): 59.32  25.33s, mean ± SD) pattern in the CBT lesions, with a high area under curve (AUC) of 672.74  145.72 mm2 (mean ± SD). In comparison with CDU, CEUS was superior in identifying Shamblin type I or III CBT lesions (2=13.959, p=0.007). It detected a significant difference in AUC between moderate and marked vascularity groups (563.33  102.63 vs. 716.50  139.26, t=2.428, p=0.025.), while CDU observed no significant difference between these two groups. Although CDU was more sensitive than CEUS in detecting feeding vessels (100% vs. 88%), CEUS better visualized the origins of feeding vessels (2=9.162, p=0.010). Conclusion: CEUS can better investigate the Shamblin type and vascularity of CBT lesions than CDU. CBTs displayed a fast wash-in, slow wash-out pattern with high AUC in the TIC analysis in CEUS mode. CDU is more sensitive in detecting feeding vessels than CEUS, while CEUS can better visualize the origins of feeding vessels.